2013
DOI: 10.1186/1471-2474-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Improved health outcomes with Etanercept versus usual DMARD therapy in an Asian population with established rheumatoid arthritis

Abstract: BackgroundPatient reported outcomes (PROs) are especially useful in assessing treatments for rheumatoid arthritis (RA) since they measure dimensions of health-related quality of life that cannot be captured using strictly objective physiological measures. The aim of this study was to compare the effects of combination etanercept and methotrexate (ETN + MTX) versus combination synthetic disease modifying antirheumatic drugs (DMARDs) and methotrexate (DMARD + MTX) on PRO measures among RA patients from the Asia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
(32 reference statements)
3
26
0
2
Order By: Relevance
“…Bae et al performed an open label study with RA adult patients who showed inadequate response to oral methotrexate (MTX), and concluded that those treated with etanercept (a TNF-alpha inhibitor)+MTX presented a statistically significant decrease in depression compared to those treated with another disease modifier anti-rheumatic drug+MTX [115]. Similar findings were published by Machado et al using a study design similar to the previous, highlighting a significant improvement in depression [116].…”
Section: Depression and Rheumatoid Arthritismentioning
confidence: 58%
“…Bae et al performed an open label study with RA adult patients who showed inadequate response to oral methotrexate (MTX), and concluded that those treated with etanercept (a TNF-alpha inhibitor)+MTX presented a statistically significant decrease in depression compared to those treated with another disease modifier anti-rheumatic drug+MTX [115]. Similar findings were published by Machado et al using a study design similar to the previous, highlighting a significant improvement in depression [116].…”
Section: Depression and Rheumatoid Arthritismentioning
confidence: 58%
“…Meta-analysis of RCTs of adjunctive treatment with anti-cytokine therapy Of three trials [48][49][50] that used anti-cytokine drugs as adjunctive treatment, two provided enough data for meta-analysis (Figure 2b). 49,50 Both of these studies compared combination of etanercept and a DMARD (n = 544) with DMARD alone (n = 405).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this, only 1 bias factor contributed to heterogeneity and had a statistically significant impact on the outcomes. This bias involved 2 studies, which were performed in Asia and Latin America, in patients with long disease duration, an inadequate response to previous DMARDs, and no treatment with a course of GC (11,12,16). In contrast, the other studies (3,4,9,10,13,15) were performed in North America and Europe, and generally in DMARD-naive early arthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses showed heterogeneity at 6 months, but few at 12 and 24 months. At 6 months, heterogeneity disappeared after the elimination of studies or treatment arms not using GC (3,11,12,16), which resulted in nonsignificant differences between a TNF inhibitor plus methotrexate and combination DMARD treatment (Figures 4 and 5, and Supplementary Figures 1 and 2), with the exception of radiographic progression ( Figure 3) and ACR70 response, (Supplementary Figure 3).…”
mentioning
confidence: 99%